What could mathematics be for it to function in distinctively mathematical scientific explanations?. (June 2021) - Lange, Marc
Highlights: Investigates what mathematical facts could be for them to figure in such "distinctively mathematical" explanations. Argues that neither platonism nor representationalism can take "distinctively mathematical explanations" as genuine. Argues that Aristotelian realism allows mathematical facts to be explainers in distinctively mathematical explanations.